CORRELATION ANALYSIS OF BLOCK PUNCH INDEX TESTING RESULT TO UNIAXIAL COMPRESSIVE STRENGTH, BRAZILIAN TENSILE STRENGTH, AND POINT LOAD INDEX - Sebastian Veron, Jerico
Rock mass classification is an important criterion to determine rock strength. One of rock mass classification parameter, especially according to Rock Mass Rating by Bieniawski (1973) is uniaxial compressive strength (UCS) value. UCS test requires big size of speciment (L=2D). Sometimes, it is difficult to obtain large specimens, especially for rocks that taken from weak plane, layered rocks, or fractured rocks. To covercome these fediciencies, Taselaar (1982) and van der Schrier (1988) initiates rock testing using blcok punch index (BPI) with specimens diamter between 42-54 mm and specimens thickness between 5-15 mm. This BPI test is aimed to obtain a conversion equation to estimate UCS value. Besides that, this test is also intended to obtain a regression equation to estimate brazilian tensile strenth value and point load index value. As a comparison, correlation equation of UCS to PLI and BTS to PLI will be made to compare the accuary between PLI and BTS as index tests. The results of data processing obtained the correlation equation of BPI to UCS is UCS = 19,539 e0,3109BPI (R² = 0,3914), the correlation equation of BPI to BTS is BTS = 1,7581 e0,2717BPI 3 (R² = 0,3182), and the correlation equation between BPI and PLI is PLI adalah PLI = 0,7433e0,5045BPI (R² = 0,6215). Meanwhile, the UCS = 23,585e0,14595PLI (R² = 0,8708) and the correlation equation of PLI to BTS is BTS = 1,4451e0,187PLI (R² = 0,8426).